On the solution of an f(r) theory of gravity motivated by gravitational waves in spherically symmetric space-time - Aditya Mani Mishra (Boletim da Sociedade Paranaense de Matemática, 2020)
There are many modification of Einstein theory have been established which explain the behavior of universe realistically or hypo-theoretically. Out of those, an f(R) theory of gravity based on non-conformal invariance of gravitational waves has been developed. We attempted to find the solution of this theory for spherically symmetric spacetime in vacuum and compared its result to Einstein theory. We have concluded that solution is consistent with Newtonian limit at large distance from source. Solution predicts two horizon in the spacetime, none of them coincides with Schwarzschild counterpart. However, as this f(R) theory converges to Einstein theory, these horizons coincide.